Database‐Driven Materials Selection for Semiconductor Heterojunction Design. Issue 10 (6th August 2018) - Shapera, Ethan P.; Schleife, André
Abstract: Heterojunctions are at the heart of many modern semiconductor devices with tremendous societal impact: Light‐emitting diodes shape the future of energy‐efficient lighting, solar cells are promising for renewable energy, and photoelectrochemistry seeks to optimize efficiency of the water‐splitting reaction. Design of heterojunctions is difficult due to the limited number of materials for which band alignment is known, and the experimental and computational difficulties associated with obtaining this data. Band alignment based on branch‐point energies ( E BP ) is shown to be a good and efficient approximation that can be obtained using data from existing electronic‐structure databases. Errors associated with this approach are comparable to those of expensive first‐principles computational techniques and experiments. E BP alignment is then incorporated into a framework capable of rapidly screening existing online databases to design semiconductor heterojunctions. The method is showcased for five different prototype cases: Transport layers are successfully predicted for CdSe‐ and InP‐based LEDs, and for CH3 NH3 PbI3 ‐ and nanoparticle PbS‐based solar absorbers. In addition, Cu2 O as a possible hole‐transport layer for solar cells is examined. The framework addresses the challenge of accomplishing fast materials selection for heterostructure design by tying together first‐principles calculations and existing online materials databases. Abstract : This work shows that the branch‐point energy is an accurate and efficient method for determining band alignment of semiconductors, with reliability comparable to experimental and first‐principles results. Branch‐point alignment is incorporated into a framework capable of rapidly screening existing online databases to design semiconductor heterostructures. The method is showcased for five prototypical example heterostructures and compared with existing literature.